Determinants of Teenage Pregnancy in Indonesia - Nikmatur Rohmah1,2, Ah Yusuf3 , Rachmat Hargono4 , Agung Dwi Laksono5 , Masruroh6 , Ilyas Ibrahim7 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The phenomenon of teenage pregnancy in Indonesia has increased annually, but only a few studies that indicate its predictors. The present research aimed at anlyzing the determinants of teenage pregnancy in Indonesia. The study used secondary data obtained from the Indonesian Demography and Health Survey (IDHS) in 2017. The independent variables are as follows age, wealth status, education, occupation, and marital status. On the other hand, the dependent variable is teenage pregnancy. The data were analyzed using binary logisctic regression. It was found that age is a significant determinant of teenage pregnancy. The richest teenager has 0.61 higher possibility of getting pregnant than the poorest. A teenager with higher education is 0.03 times more possible to get pregnant than one that has not gone to school before. Moreover, a working teenager has the possibility to get pregnant higher than that of not working teenager by 1.47 times. The present study empirically proves that marital status is not a determinant of teenage pregancu. While the four other variables, such as age, lower wealth status, no education, and working have been proven as determinants of teenage pregnancy in Indonesia.